(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The fruit avocado, which is also known as alligator pear and avocado, has a few exciting traits, including its pear-like form and inexperienced rough skin. Avocado fruit is originally from Mexico and is, a tree of the own family Lauraceae. they may be more often than not grown in warm climates, around 28-32 and they can’t tolerate freezing temperatures. this is why, they were domesticated 5.000 years in the past. Avocado fruits have greenish or yellowish flesh with a buttery consistency and a wealthy nutty flavor. all around the world, they’re utilized in food and salads, and in many elements of the sector, they’re eaten as a dessert. Avocados provide thiamin and riboflavin, and it’s miles a supply of nutrition A, C, E, and in a few varieties, the flesh contains as much as 25 percent unsaturated oil. Avocado has more than 10 varieties, however, the most famous type amongst them is avocado, because of its creamy consistency and excessive flavor.